2005
DOI: 10.1523/jneurosci.0028-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Long-Lasting Synaptic Plasticity and Cognition in Mice Lacking the Mental Retardation GenePak3

Abstract: Mutations in the Pak3 gene lead to nonsyndromic mental retardation characterized by selective deficits in cognition. However, the underlying mechanisms are yet to be elucidated. We report here that the knock-out mice deficient in the expression of p21-activated kinase 3 (PAK3) exhibit significant abnormalities in synaptic plasticity, specifically hippocampal late-phase long-term potentiation, and deficiencies in learning and memory. A dramatic reduction in the active form of transcription factor cAMP-responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
166
1
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(180 citation statements)
references
References 71 publications
9
166
1
2
Order By: Relevance
“…More recently, mice lacking the PAK3 gene were generated, and analysis of these mice showed selective impairment in late-phase hippocampal LTP, a distinct form of long-term synaptic plasticity involving new gene expression. Surprisingly, in this mice knockout model, no obvious deficits in neuronal structures were observed [57]. The differences seen with regards to spine morphology between the knockout and RNAi studies could potentially reflect differences between a homogeneous and a heterogeneous cell population, respectively, or could be attributed to compensatory mechanisms in the knockout mice.…”
Section: Pak3mentioning
confidence: 68%
“…More recently, mice lacking the PAK3 gene were generated, and analysis of these mice showed selective impairment in late-phase hippocampal LTP, a distinct form of long-term synaptic plasticity involving new gene expression. Surprisingly, in this mice knockout model, no obvious deficits in neuronal structures were observed [57]. The differences seen with regards to spine morphology between the knockout and RNAi studies could potentially reflect differences between a homogeneous and a heterogeneous cell population, respectively, or could be attributed to compensatory mechanisms in the knockout mice.…”
Section: Pak3mentioning
confidence: 68%
“…46 For PAK3 (p21-activated kinase), a member of PAK protein family that are activated by the two small RhoGTPases Rac and Cdc42 (cell division cycle 42 ), the contribution in synapse formation and plasticity was clearly demonstrated by two groups. 44,45 Using transient 45 showed that PAK3 is localized at dendritic spines, and that PAK3 inactivation results in formation of abnormal dendritic spines and a reduced spontaneous synaptic activity and defective long-term potentiation (LTP). Meng et al 44 generated a knockout mice model deficient for PAK3 and showed that this model exhibits significant abnormalities in synaptic plasticity, especially hippocampal late-phase LTP, and deficiencies in learning and memory.…”
Section: Synaptic Structure and Function And Mental Retardationmentioning
confidence: 99%
“…5 -8 PAK3 gene transcripts encode p21-activated kinase (PAK) protein isoforms shown to be critical downstream rGTPases effectors that link Rac1 and Cdc42 to actin cytoskeleton and MAP kinases cascades. 5,9 The most investigated PAK3 protein isoform contains 544 amino acids with two critical domains, consisting of an N-terminal regulatory region that includes a CRIB motif that binds to GTP bound forms of Cdc42 and Rac1, and a C-terminal catalytic domain with a serine/threonine (STK) protein kinase domain. 10 To our knowledge, the described PAK3 mutations include one nonsense mutation (p.R419X) and three missense mutations located either in the regulatory or the catalytic domain without any evidence of correlation with the severity of the phenotype.…”
Section: Introductionmentioning
confidence: 99%